Peran Good Corporate Governance dalam Menurunkan Credit Risk pada Bank yang Go Public di Bursa Efek Indonesia - Dika Zanuar Virgantara; Mutamimah Mutamimah (Jurnal Bisnis dan Ekonomi, 2022)
This study aims to examine and analyze the role of good corporate governance in moderating the influence of the loan to deposit ratio, capital adequacy ratio, inflation and gross domestic product on the reduction of credit risk in banking companies that go public on the Indonesia Stock Exchange. The population in this study are all companies going public on the Indonesian Stock Exchange. The sampling technique used purposive sampling, with the criteria for banking companies going public in 2008-2021, so that 308 observations were obtained. The type of data is panel data which is a combination of cross section data and time series data, so the statistical technique uses E-views software. After passing the classic assumption test and conducting tests to choose the best results, the results show that the loan to deposit ratio has an effect on credit risk, but the capital adequacy ratio, inflation and gross domestic product have no effect on credit risk. In addition, GCG strengthens the influence of the loan to deposit ratio in reducing credit risk, but GCG actually weakens the influence of the capital adequacy ratio in reducing credit risk.